KONSEP DASAR EVALUASI PEMBELAJARAN SD N 200103 PADANGSIDIMPUAN - Siregar, Rahman; Harahap, Asriana (Thiflun : Jurnal Pendidikan Dasar, 2023)
Based on observations that have been made with interviews with teachers conducted at SD Negeri 200103 Padangsidimpuan, which relates to the basic concept of evaluation. Based on the results of interviews conducted by researchers to teacher evaluation consists of measurement and assessment. In the context of learning, evaluation has a very important and strategic position, because it is included in the steps of learning. The aim is to find out the effectiveness and efficiency of the learning system. The environment includes evaluating learning programs, learning processes and learning outcomes. In general, the evaluation principle consists of continuity, comprehensive, fair, objective, cooperative and practical. Specifically, the principle consists of cohesiveness, coherence, pedagogy, and accountability. In terms of type, evaluation of learning consists of evaluating planning, development, monitoring, impact, efficiency, and comprehensive programs.Â Keywords: Learning Evaluation, Evaluation Objectives, Evaluation Functions, Evaluation Principles, Scope of Evaluation.